Prospecting cellulose fibre-reinforced composite membranes for sustainable remediation and mitigation of emerging contaminants. (October 2022) - Zhang, Shizhong; Vanessa, ChansaKayeye; Khan, Adnan; Ali, Nisar; Malik, Sumeet; Shah, Sumaira; Bilal, Muhammad; Yang, Yong; Akhter, Mohammed Salim; Iqbal, Hafiz M.N.
Abstract: Many environmental pollutants caused by uncontrolled urbanization and rapid industrial growth have provoked serious concerns worldwide. These pollutants, including toxic metals, dyes, pharmaceuticals, pesticides, volatile organic compounds, and petroleum hydrocarbons, unenviably compromise the water quality and manifest a severe menace to aquatic entities and human beings. Therefore, it is of utmost importance to acquaint bio-nanocomposites with the capability to remove and decontaminate this extensive range of emerging pollutants. Recently, considerable emphasis has been devoted to developing low-cost novel materials obtained from natural resources accompanied by minimal toxicity to the environment. One such component is cellulose, naturally the most abundant organic polymer found in nature. Given bio-renewable sources, natural abundance, and impressive nanofibril arrangement, cellulose-reinforced composites are widely engineered and utilized for multiple applications, such as wastewater decontamination, energy storage devices, drug delivery systems, paper and pulp industries, construction industries, and adhesives, etc. Environmental remediation prospective is among the fascinating application of these cellulose-reinforced composites. This review discusses the structural attributes of cellulose, types of cellulose fibrils-based nano-biocomposites, preparatory techniques, and the potential of cellulose-based composites to remediate a diverse array of organic and inorganic pollutants in wastewater. Graphical abstract: Image 1 Highlights: Pollutant such as toxic metals, dyes, pharmaceuticals, pesticides cause threats to the living ecosystems. Cellulose-based composite membranes exhibit fascinating structural and functional attributes. Cellulose fibre-reinforced membranes are given to remediate environmentally toxic pollutants.